2016
DOI: 10.1159/000444263
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Activity of Antibiotics in Cerebrospinal Fluid in vitro

Abstract: Background: In vitro studies suggest that antimicrobial activity of antibiotics meant to treat central nervous system infections such as meningitis or ventriculitis may be altered by cerebrospinal fluid (CSF). This could explain the reason behind the often observed discrepancies between the activity of antibiotics determined in artificial growth media in vitro, and their sometimes reduced clinical efficacy in CSF in vivo. If conducted in CSF, in vitro microbiological investigations might predict the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…To test this, we performed in vitro growth curves in artificial CSF but found no difference between growth of cdk8 and control strains (Fig. 9B) (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this, we performed in vitro growth curves in artificial CSF but found no difference between growth of cdk8 and control strains (Fig. 9B) (30).…”
Section: Resultsmentioning
confidence: 99%
“…For all studies, cryptococcal strains were grown overnight in YPD medium (1% [wt/vol] Bacto yeast extract, 2% [wt/vol] d -glucose, 2% [wt/vol] Bacto Peptone in ddH 2 O) at 30°C in room air with shaking at 230 rpm. For growth curves, cells were sedimented at 1,000 × g (25°C, 3 min), washed with phosphate-buffered saline (PBS), and adjusted to 1 × 10 5 cells/ml before growth at 30°C in room air in YPD or at 37°C, 5% CO 2 in DMEM, RPMI, or sterile artificial cerebrospinal fluid (ACSF) (124 mM NaCl, 2.5 mM KCl, 2 mM MgSO 4 , 1.25 mM KH 2 PO 4 , 26 mM NaHCO 3 , 10 mM d -glucose, 4 mM sucrose, 2.5 mM CaCl 2 , 360 mg/liter sterile BSA, 100 mM creatinine, 6 mM urea) (30). Cell counts were measured at the indicated time points, and growth curves were performed twice.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown in a rabbit model that a high concentration of vancomycin is present in the cerebral spinal fluid of inflamed meninges [ 20 ]. Therapeutic concentrations of vancomycin in ascitic, pericardial, pleural, and synovial fluids are greater than 2.5 mg/L in humans [ 21 ].…”
Section: Pharmacokinetics and Pharmacodynamics Of Vancomycinmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) might also act as an important environment for antibiotic activity, especially in the treatment of central nervous infections, such as meningitis or ventriculitis. Concerns over equality of the antibiotic activity in vitro and its clinical efficacy have been discussed in the review by Matzneller et al [ 11 ]. Indeed, one study showed that rifampicin concentrations above the MIC were required to achieve bacterial killing of S. aureus in CSF (with CO 2 ) compared to pure MHB.…”
Section: Published In Vitro Studiesmentioning
confidence: 99%